Development of a Physiological Age-Grading System for Nezara viridula (Hemiptera: Pentatomidae). Issue 5 (16th September 2020) - Grodowitz, Michael J; Elliot, Brad; Evans, Richard; Rojas, Guadalupe; Morales Ramos, Juan
Abstract: The southern green stink bug (SGSB), Nezara viridula (L.), is an important agricultural pest in the United States. Limited information is available on the morphology of the female's reproductive system in relation to morphological changes associated with the number of eggs produced and egg masses oviposited. The ability to assess reproductive health and reproductive status based on ovarian morphology (i.e., physiological age-grading) can be an important tool for evaluating field populations and laboratory colonies intended for the application of different management strategies and experimental trials. Thus, the goal of this study was to develop a physiological age-grading system for SGSB. Females aged from 0 to 79 d chronologically randomly selected from laboratory colonies and dissected to assess ovarian morphology. Specific morphological differences in ovarian structures including differentiation of the ovarioles, deposition of yolk in the most proximal follicle, quantity and appearance of follicular relics, expansion of the lateral oviducts, and number of developing follicles per ovariole were related to chronological age, the number of eggs produced and number of egg masses. Based on specific combinations of these morphological characteristics, the continuum of ovarian development was divided into three nulliparous (i.e., 'no eggs'; N1, N2, and N3) and three parous stages (i.e., 'with eggs'; P1, P2, and P3). Direct relationships were noted between number of eggs produced and physiological age with over 7-fold higher number of eggs and 14-fold higher number of egg masses associated with the P2 and P3 stages, respectively.